Corneal oxidative stress, inflammation, and senescence as key drivers of ocular pathology in a chronic graft-versus-host disease model - Rong Wu; Shuwan Liu; Zhan Shen; Yinghan Zhao; Jing Hong; Jiao Ma (BMC Ophthalmology)
Abstract Background Chronic graft-versus-host disease (cGVHD) is a severe complication of allogeneic hematopoietic stem cell transplantation, frequently associated with severe dry eye syndrome. Using a murine cGVHD model, this study investigates the roles of oxidative stress, inflammation, and cellular senescence in corneal damage. Methods A cGVHD mouse model was established by transplanting bone marrow cells and splenocytes from male C57BL/6J (H-2b) donors into lethally irradiated female BALB/c (H-2d) recipients. Clinical parameters (including survival rates and tear volume), corneal damage(assessed by fluorescein staining score), and ocular tissue inflammation/fibrosis (via histological analysis) were evaluated. Oxidative stress markers (8-OHdG), 4-Hydroxynonenal (4HNE), antioxidant enzymes (catalase), Nuclear factor erythroid 2-related factor 2 (Nrf2), senescence-related genes (P16INK4A, P38 MARK), and inflammation-related proteins (IL6, IL8, NF-κB) were detected using immunohistochemistry (IHC), qPCR, and SA-β-gal staining. Gene Ontology (GO) enrichment analysis was performed to illustrate alterations in gene expression. Results Chronic ocular GVHD (coGVHD) mice presented with higher clinical scores, characterized by weight loss, skin lesions, and systemic symptoms. They also exhibited reduced tear volume and exacerbated corneal epithelial damage. Histological analysis showed significant inflammation and fibrosis in Meibomian glands (MGs) and lacrimal glands (LGs). Upregulation of 8-OHdG and 4HNE, along with downregulation of catalase and Nrf2, was observed, indicating enhanced oxidative stress and compromised antioxidant defense. Elevated levels of pro-inflammatory markers (IL-6, IL-8, NF-κB), the pro-fibrotic marker α-SMA, and senescence markers (P16INK4A, P38 MARK) were detected. These findings suggest a complex interplay among inflammation, fibrosis, and cellular senescence in the pathogenesis of coGVHD corneas. Bioinformatics analysis revealed significant changes in gene expression related to oxidative stress, inflammation, and senescence in coGVHD corneas. Conclusion The study elucidates the central roles of oxidative stress, inflammation, and cellular senescence in corneal pathology in cGVHD, identifying potential targets for innovative therapeutic strategies. Clinical trial number Not applicable.